Prospects of Nuclear Energy Development in Asia: Comparison with “Green Energy” - Panina, Olga V.; Prokofiev, Stanislav E.; Barmenkova, Natalia A.; Krasyukova, Natalia L.; Kushchev, Nikolay P. (International Journal of Energy Economics and Policy, 2020)
Nuclear energy is an important part of energy balance of Asian countries. But at the same time, concerns about the safety of nuclear energy production are high, and the future of nuclear energy in Asia is unclear. New trends in the development of “green energy” production, especially in the most dynamically developing countries of Asia, create a high competition with nuclear energy in the region. The authors aim at a general analysis of the energy markets of leading Asian countries, which have a significant share of nuclear energy production in their energy balance – China, Japan, Korea and India. The second tool that the authors use is an econometric analysis of energy production in the studied countries. These two aspects of the energy sector analysis allow the authors to comprise the results and to form a vision of a more promising sector of the energy industry. Based on these results, the authors give a number of recommendations on the development of nuclear energy production in the studied countries. One of the main conclusions is that nuclear energy should be used as a reserve source of energy in Asian economies until they reach a high share of “green energy” in energy balance. Keywords: Nuclear energy, “green energy”, Asia, policy, energy market JEL Classifications: Q40; Q47; P18; P28; P48 DOI: https://doi.org/10.32479/ijeep.9983